Women’s experiences of living with adenomyosis and perceptions of the diagnostic journey: a scoping review - Tim J Croudace; Margaret A Taylor; Margot McBride; Fiona E Muir (BMJ Open)
Objectives Uterine adenomyosis is a common gynaecological disease that can be debilitating. It is poorly understood and may be overlooked in clinical settings. A research gap exists as there are currently no published scoping reviews on perceptions and experiences early in the illness course. As part of a professional doctorate thesis, the aim of this review is to systematically retrieve and describe available literature, exploring the impact of living with adenomyosis and perceptions of the diagnostic journey.Design A scoping review is conducted using JBI methodology.Data sources Medline, CINAHL Plus, Web of Science, Google Scholar, Cochrane library, JBI and PROSPERO databases, EThOS online and Google. Searches were made from database inception to July 2023.Eligibility criteria The characteristics of the evidence sourced were deliberately broad. Studies exploring the experiences and perceptions of women diagnosed with adenomyosis were considered.Data extraction and synthesis Titles and abstracts were initially screened. Subsequently, eligibility was clarified through methods section inspection, and the remaining studies were read in depth. A manual hand-search of references of selected studies was conducted. Prespecified data were extracted, charted and categorised into themes.Results Six eligible studies were found, with themes describing impact and burdens, as well as several categories of unsupported needs. No studies specifically focused on perceptions of the diagnostic journey, but some eligible studies made minor reference to this and are included.Conclusions This review highlights the profound impact of adenomyosis and is the first to explore the lived experiences and the diagnostic journey. Understanding the burdens of disease in terms of perceptions and lived experience in combination with the experiences of diagnostic interactions is vital to improving diagnostic pathways. Education with improved multidisciplinary collaboration and further qualitative and case study research will be crucial to achieve this goal.Registration A priori protocol was registered (https://doi.org/10.17605/OSF.IO/2UDYN) and published (https://doi.org/10.1136/bmjopen-2023-075316).